Towards responsive and responsible administration: revamping civil services - Eswara Reddi, Agarala (1997)
The author discusses the basic principle of administration in a democracy is that administration should always be in accordance with the law. When ministers tend to depart from established norms and procedures, it is the duty of civil servants to point it out to them. Unfortunately, a new trend has emerged in Indian Administration where some ministers seem to think that laws and regulations can be modified or even ignored to suit their convenience. - Reproduced
Keywords: Public administration; Administrative reform; Civil service - India; Civil service